Esterification of oleic acid and palm fatty acid distillate-oleic acid blend using sulfated titania-silica catalyst - Waziri, Jibrin (2016)
The synthesis of biodiesel from low cost feedstocks containing high free fatty acid is gradually gaining global acceptance as a worthwhile process route capable of keeping biodiesel production cost and its product price below that of petroleum diesel. The high free fatty acid content of these feedstocks however makes them difficult to process using the conventional high activity base catalysts. Sulphuric acid has been widely employed in the esterification of oils containing high free fatty acids to produce biodiesel. However, the major demerits associated with the use of sulphuric acid are its corrosiveness and environmental unfriendliness. In this study, biodiesel was synthesized from the individual methanolysis of oleic acid, and PFAD-oleic acid blend in the ratio 8:2 using sulfated titania-silica catalyst. This catalyst was prepared by reacting 0.5M solution of titanium isopropoxide with silica and then sulfated with 0.5 M sulphuric acid. The catalyst was then characterized by FE-SEM, XRD, BET, TGA, TPD - NH3 and FTIR respectively. The esterification was carried out in a three-neck round bottom flask and was well stirred. The variables investigated are molar ratio of oleic acid and PFAD-Oleic acid blend to methanol, catalyst loading and reaction time; while the reaction temperature and stirring rate were kept constant at 65 oC and 200 rpm respectively. The process was optimized using response surface methodology (RSM) based on Box Behnken design (BBD) to explicitly depict the interactions between the independent variables and the responses. The resulting biodiesel yield was determined using GC/FID and the conversion was determined through volumetric analysis. The optimum values predicted for methyl oleate yield and oleic acid conversion from the esterification of oleic acid are 81.04% and 92.14%. While the optimum values for methyl oleate yield, methyl palmitate yield and PFAD-oleic acid conversion obtained from the esterification of PFAD-oleic acid blend are 90.04%, 91.92% and 96.84% respectively.